Overall migration in commercially-available instant cup noodle containers - Gualberto, Selina Rabin S.
This study was done to evaluate the safety of instant cup noodles in terms of overall migration. Migration is the release of monomers and additives called migrants from the packaging material into the food. Some migrants can cause quality deterioration and potentially harmful effects on consumer health. Nineteen representative samples of Philippine-manufactured commercially-available instant noodle cups were tested for overall migration. Out of 19, eight were made out of polypropylene and 11 were polyethylene-lined paperboard. Overall migration (OM) testing was done using the article filling method with testing conditions of 30 minutes at 100 °C. OM values ranged from 0.00 to 2.47 mg/dm2. All samples were found to be within the OM limits of 7.75 mg/dm2 and 10 mg/dm2 specified by the US FDA and EU, respectively. No trends were observed between the physical properties or type of packaging materials and OM values. All tested instant noodle cup containers were considered safe for use as long as preparation and use instructions are properly followed. Studies on the specific migration of the samples and OM of lids are recommended.